The analysis of properties of arsenates and antimonatеs of barium based on diagrams of the partial pressures - Omarov, Kh.B.; Absаt, Z.B.; Aldabergenova, S.K.; Rakhimzhanova, N.Zh.; Karimova, A.B. (KSU publ., 2014)
By results of thermodynamic calculations diagrams the partial pressure of systems Ba–O2–SO2–As2, Ba–O2–SO2–Sb2 are constructed. The analysis of interactions of compounds of antimony and arsenic in systems Ba–O2–SO2–As2, Ba–O2–SO2–Sb2 is carried out at 25 ºC and 1 atm. general pressure. Areas of stability of arsenate and arsenite of barium, and also antimonite and an antimonat of barium are defined.
Keywords: thermodynamic analysis; arsenite; arsenate; antimonite; stability; antimonat; diagrams of the partial pressures